Analysis Of Financial Ratio In Palm Companies On The Indonesia Stock Exchange at PT. Agra Agro Lestari TBK Over Period 2015-2022 - Raharjo , Budi; Musthofa , Zaenal; Digdowiseiso , Kumba (CV ODIS, 2024)
The aim of this research is to analyze the influence of Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Equity (ROE) on Earning Per Share (EPS) at the palm oil company PT. Astra Agro Lestari Tbk which is listed on the Indonesia Stock Exchange. The data used in this research comes from the annual financial report of the palm oil company PT. Astra Agro Lestari Tbk during the period 2015 - 2022. The research method used is multiple regression analysis to analyze financial reports in terms of Liquidity Ratio, Coverage Ratio, Solvency Ratio, Profitability Ratio, Market Ratio and Efficiency Ratio. It is hoped that the results of this research will provide a deeper understanding of the factors that influence EPS at the palm oil company PT. Astra Agro Lestari Tbk on the Indonesian Stock Exchange. The practical implication of this research is to provide guidance to financial managers of palm oil companies PT. Astra Agro Lestari Tbk in managing financial ratios such as Liquidity Ratio, Coverage Ratio, Solvency Ratio, Profitability Ratio, Market Ratio and Efficiency Ratio.